Corporate science in the patent system: An analysis of the semiconductor technology - Antonio Della Malva; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Corporate scientific publications are often presented as a strategic means for firms to create prior art with the objective to prevent others from patenting related inventions. This presumes that corporate publications enter the pool of prior art which is relevant to judge the novelty of patent applications at the patent office and that corporate science has the power to block patent applications. This paper analyses for the first time whether the presumed mechanism behind corporate publications as a means to preempt patents works. With focus on the semiconductor technology our results show that scientific publications by corporations challenge the novelty of patent applications at the European Patent Office (EPO) significantly more than other pieces of prior art. Detailed information from the EPO patent examination procedure allows us to show that corporate publications threaten the novelty of patent applications if combined with other pieces of prior art like patents (rather than as standalone documents). This supports the view that corporate scientific publishing can be an effective means for firms to protect their freedom to operate if used as a complementary part of a firms' overall IP protection strategy as proposed by scholars in the field of law and management science.
Keywords: O34; O32; 330; defensive corporate publishing; freedom to operate; patents; semiconductor; Industrielle Forschung; Publikationsanalyse; Patent; Strategie; Halbleiterindustrie; EU-Staaten